2022
DOI: 10.1002/epi4.12600
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID‐19 measures on the hospitalization of patients with epilepsy and status epilepticus in Thailand: An interrupted time series analysis

Abstract: Objective To investigate the effect of Coronavirus disease 2019 (COVID‐19) measures on the hospitalization of patients with epilepsy and status epilepticus (SE). Methods This interrupted time series design included data from the Thai Universal Coverage Scheme electronic database between January 2017 and September 2020. The monthly hospitalization rate of epilepsy and SE was calculated by the number of hospitalizations divided by the midyear population. Segmented regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The most remarkable drop was found amongst children, whereas that amongst the older adults was trivial. Also, there was no significant change in hospitalisation rate in severe presentation of epilepsy like status epilepticus [ 16 ]. Sukmanee et al reported a significant decline in the number of OP visits of the patients under the Universal Coverage Scheme—the main insurance arrangement for most Thai citizens—for many diagnostic groups during the lockdown period in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The most remarkable drop was found amongst children, whereas that amongst the older adults was trivial. Also, there was no significant change in hospitalisation rate in severe presentation of epilepsy like status epilepticus [ 16 ]. Sukmanee et al reported a significant decline in the number of OP visits of the patients under the Universal Coverage Scheme—the main insurance arrangement for most Thai citizens—for many diagnostic groups during the lockdown period in 2020.…”
Section: Discussionmentioning
confidence: 99%